1995
DOI: 10.1177/154193129503900201
|View full text |Cite
|
Sign up to set email alerts
|

Age, Expertise, Structural Similarity, and Time-Sharing Efficiency

Abstract: Interactive effects of age, expertise, and structural similarity on time-sharing efficiency were examined. Half of 90 subjects who ranged from age 20 to 80 years were nonpilots. The other half were pilots who were considered to have expertise in time-sharing. Five dual tasks were selected to represent various cognitive aspects of flight performance and to represent various degrees of structural similarity defined by Wickens' multiple resource model. Several main findings were of note. One, time-sharing efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, in the Szafran study there were also no significant age-related changes in detection threshold of critical flicker fusion frequency and minimum perceptible interflash interval and recognition thresholds for tachistoscopic displays for simple stimuli such as shapes, numbers, letters, and words. For more complex perceptual-motor tasks, in a heterogeneous sample of pilots, older pilots performed worse (had larger deviations) than younger pilots on a horizontal tracking task and a vertical tracking task (Tsang & Shaner, 1995; Tsang et al, 1995). In a large sample of commercial airline and military pilots ( N = 90 and N = 454, respectively), there were significant correlations between pilot age and several aviation-related tasks including object identification (−.29), spatial orientation (−.14), instrument comprehension (−.33), and reoriented reading clocks (−.09; Glanzer, and, & Glaser, 1959).…”
Section: Pilot Cognition and Agingmentioning
confidence: 91%
“…However, in the Szafran study there were also no significant age-related changes in detection threshold of critical flicker fusion frequency and minimum perceptible interflash interval and recognition thresholds for tachistoscopic displays for simple stimuli such as shapes, numbers, letters, and words. For more complex perceptual-motor tasks, in a heterogeneous sample of pilots, older pilots performed worse (had larger deviations) than younger pilots on a horizontal tracking task and a vertical tracking task (Tsang & Shaner, 1995; Tsang et al, 1995). In a large sample of commercial airline and military pilots ( N = 90 and N = 454, respectively), there were significant correlations between pilot age and several aviation-related tasks including object identification (−.29), spatial orientation (−.14), instrument comprehension (−.33), and reoriented reading clocks (−.09; Glanzer, and, & Glaser, 1959).…”
Section: Pilot Cognition and Agingmentioning
confidence: 91%
“…Studies have revealed that not only does the amount of knowledge increase with experience, the qualitative nature of knowledge organization becomes more sophisticated (Schvanevelt, 1985;Sherry & Polson, 1999). Hardy and Parasuraman (1997) ability (Tsang & Shaner, 1995), speed of processing (Taylor et al, 1994), attention (Knapp & Johnson, 1996), and both psychomotor ability and general intelligence (g) (Caretta & Ree, 2003). Yakimovitch et al (1994) were among the very first to use a method to investigate these complex interactions between individual, expertise and flight performance.…”
Section: Known Signatures Of Expertisementioning
confidence: 99%